Application of Er:YAG and Er, Cr:YSGG lasers in cavity preparation for dental tissues: a literature review - Santos, Carla Raquel dos [UNESP]; Tonetto, Mateus Rodrigues [UNESP]; Presoto, Cristina Dupim [UNESP]; Bandéca, Matheus Coelho; Oliveira Júnior, Osmir Batista de [UNESP]; Calabrez-Filho, Saturnino [UNESP]; Andrade, Marcelo Ferrarezi de [UNESP] (Jaypee Brothers Medical Publishing, 2012)
The laser has been widely used in many specialties of dentistry and several wavelengths have been investigated as a substitute for high-speed handpiece. The purpose of this paper is to review the literature about the use of Er:YAG and Er,Cr:YSGG lasers in cavity preparation for dental tissues. Despite the differences in wavelength, pulse duration and energy, the morphological characteristics of the irradiated dentin surface with these lasers are comparable, as well as its effects as methods of dental caries prevention. Thus, Er:YAG and Er,Cr:YSGG lasers prepared cavities with similar effects on the dental tissue, however, further investigations about ideal irradiation conditions are needed for both lasers.
Keywords: Lasers; Dental caries; Dentin